An Analysis of Associative Meaning in Tourism Magazine - Dachi, Elviran Suriani; Nawung, Agnes; Sukarsih, Ni Nyoman Tri; Awololon, Yohanes; Lindawati, Ni Putu (Denpasar Institute, 2025)
This study examined associative meanings in the English-Indonesian edition of the tourism magazine Api Bali (February–March 2020). Using a qualitative approach grounded in Geoffrey Leech’s (1981) theory, the analysis focused on identifying connotative, social, affective, and collocative meanings. The findings revealed that word and phrase choices were strategically employed to uphold the prestige of Bali’s tourism products and destinations. Affective meanings, in particular, were used to create a positive emotional appeal and foster an optimistic perception of Bali. These results highlight the significance of associative meaning in shaping reader engagement and enhancing the communicative impact of tourism content.